2005
DOI: 10.1037/0278-6133.24.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotion and Health: Going Beyond the Negative.

Abstract: This study examined the relationships between positive emotions and health. Two positive emotions were considered, hope and curiosity, in conjunction with 3 physician-diagnosed disease outcomes: hypertension, diabetes mellitus, and respiratory tract infections. Medical data were abstracted over a 2-year period from 1,041 patient records from a multispecialty medical practice, and emotions were assessed through a mailed questionnaire. Across 3 disease outcomes, higher levels of hope were associated with a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
148
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(173 citation statements)
references
References 53 publications
(74 reference statements)
4
148
1
7
Order By: Relevance
“…These results Clin Psychol Med Settings (2012) 19:197-210 203 support emerging evidence suggesting that positive affect may be a protective factor against illnesses (Fredrickson, 1998;Pressman & Cohen, 2005;Richman et al, 2005). For example, positive affect, independent of negative affect, has been demonstrated to be inversely related to the risk of incident stroke (Ostir, Markides, Peek, & Goodwin, 2001), 10-year incidence of coronary heart disease (Davidson, Mostofsky, & Whang, 2010), mortality in medical in-patients (Scherer & Hermann-Lingen, 2009), and mortality in diabetic patients (Moskowitz, Epel, & Acree, 2008).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These results Clin Psychol Med Settings (2012) 19:197-210 203 support emerging evidence suggesting that positive affect may be a protective factor against illnesses (Fredrickson, 1998;Pressman & Cohen, 2005;Richman et al, 2005). For example, positive affect, independent of negative affect, has been demonstrated to be inversely related to the risk of incident stroke (Ostir, Markides, Peek, & Goodwin, 2001), 10-year incidence of coronary heart disease (Davidson, Mostofsky, & Whang, 2010), mortality in medical in-patients (Scherer & Hermann-Lingen, 2009), and mortality in diabetic patients (Moskowitz, Epel, & Acree, 2008).…”
Section: Discussionsupporting
confidence: 53%
“…Of these factors, individual differences in the experience and expression of various distressing emotional states-i.e., anger/hostility, depression, anxiety, and cynicism-are routinely discussed and have been found to be associated with numerous adverse health conditions, including coronary heart disease (Kubzansky & Kawachi, 2000;Suls & Bunde, 2005), high blood pressure (Jorgensen, Johnson, Kolodziej, & Schreer, 1996;Patten et al, 2009;Yan et al, 2003), asthma (Huovinen, Kaprio, & Koskenvuo, 2001;Lehrer, Isenberg, & Hochron, 1993;Loerbroks, Apfelbacher, Thayer, Debling, & Sturmer, 2009), stroke (Colantonio, Kasl, & Ostfeld, 1992;Everson, Roberts, Goldberg, & Kaplan, 1998), and diabetes (Anderson, Freedland, Clouse, & Lustman, 2001;Lustman, Frank, & McGill, 1991). However, the role and importance of positive emotions in health is less clear, although emerging evidence suggests that these emotions may serve as a protective factor against illnesses and mortality (Fredrickson, 1998;Pressman & Cohen, 2005;Richman et al, 2005). Thus, the primary objective of this study was to explore this more extensively individual differences in both negative and positive emotional states and their associations with a range of physical disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, the example from the research by Hambrick and McCord (2010) shows that the relationship between cognitive openness measured by the BIG-FIVE personality test with applying proactive strategies is very weak. Richman et al (2005) observed, that curiosity is related to lower prevalence of type 2 diabetes.Every disease, chronic in particular, may be a source of psychological stress (Heszen & Sęk, 2008). This stress is generated by both difficulties stemming from many limitations dictated by the disease, which entail lifestyle changes, and awareness of the possibility of the occurrence of future secondary difficulties concerning the somatic and psychological domains.…”
mentioning
confidence: 79%
“…However, the example from the research by Hambrick and McCord (2010) shows that the relationship between cognitive openness measured by the BIG-FIVE personality test with applying proactive strategies is very weak. Richman et al (2005) observed, that curiosity is related to lower prevalence of type 2 diabetes.…”
mentioning
confidence: 79%
“…They even promote vibrant health, 339,340 and longevity. 341,342 They both signal novel developmental opportunities and reflect optimal self-regulation, the "self-control" that predicts health, wealth and even public safety.…”
Section: Emotion and Optimal Developmentmentioning
confidence: 99%